Verbs of perception: a quantitative typological study - Norcliffe, E; Majid, A (Project MUSE, 2024)
Previous studies have proposed that the lexicalization of perception verbs is constrained by a biologically grounded hierarchy of the senses. Other research traditions emphasize conceptual and communicative factors instead. Drawing on a balanced sample of perception verb lexicons in 100 languages, we found that vision tends to be lexicalized with a dedicated verb, but that nonvisual modalities do not conform to the predictions of the sense-modality hierarchy. We also found strong asymmetries in which sensory meanings colexify. Rather than a universal hierarchy of the senses, we suggest that two domain-general constraints—conceptual similarity and communicative need—interact to shape lexicalization patterns.